Inter‐hospital variation in surgical intensity for trauma admissions: A multicentre cohort study. Issue 11 (27th August 2020) - Patton, Marie‐Pier; Moore, Lynne; Farhat, Imen; Tardif, Pier‐Alexandre; Gonthier, Catherine; Belcaid, Amina; Lauzier, François; Turgeon, Alexis; Clément, Julien
Abstract: Background: Guidelines for injury care are increasingly moving away from surgical management towards less invasive procedures but there is a knowledge gap on how these recommendations are influencing practice. We aimed to assess inter‐hospital variation in surgical intensity for injury admissions and evaluate the correlation between hospital surgical intensity and mortality/complications. Methods: We included adults admitted for major trauma between 2006 and 2016 in a Canadian provincial trauma system. Analyses were stratified for orthopaedic (n = 16 887), neurological (n = 12 888) and torso injuries (n = 9816). Surgical intensity was quantified with the number of surgical procedures <72 hours. Inter‐hospital variation was assessed with the intra‐class correlation coefficient (ICC). We assessed the correlation between the risk‐adjusted mean number of surgical procedures and risk‐adjusted incidence of mortality and complications using Pearson correlation coefficients ( r ). Results: Moderate inter‐hospital variation was observed for orthopaedic surgery (ICC = 14.0%) whereas variation was low for torso surgery (ICC = 2.7%) and neurosurgery (ICC = 0.8%). Surgical intensity was negatively correlated with hospital mortality for torso injury ( r = −.32, P = .02) and neurotrauma ( r = −.65, P = .08). A strong positive correlation was observed with hospital complications for orthopaedic injuries ( r = .36, P = .006) whereas the opposite was observed for neurotrauma ( r = −.71, P = .05). Conclusions: Results should be interpreted with caution as they may be a result of residual confounding. However, they may suggest that there are opportunities for quality improvement in surgical care for injury admissions, particularly for orthopaedic injuries. Moving forward, we should aim to prospectively evaluate adherence to guidelines on non‐operative management and their impact on mortality and morbidity.